Enhancing Quality of Agricultural Education Throught Research: Students’ Perspective - Paulino A. Oñal, Jr.; Bro. Jian Meng Yuan; Flordeliza U Ampusta; Mark Anthony G Abello; Rogelio M Magbanua Jr.; Alex S Lecciones (Future Science / FSH-PH Publications, 2026)
This study examined the relationship between the quality of agricultural education offered by the Catholic College in Murcia, Philippines, and the availability of resources through research-based learning. It was conducted by assessing the level of student satisfaction with the teaching of research-related subjects and the availability of institutional resources. Using a quantitative descriptive-correlational design, responses from 62 students were analyzed through mean scores and Pearson’s correlation coefficients. On the student level of satisfaction, the improvement of the quality of agricultural education offered by the college has the highest mean score (4.60), followed by the creation of the REXIN (Research, Extension, and Innovations) office (4.58). Furthermore, analysis shows a significant difference in the creation of REXIN Office (f=2.51, alpha=0.05) compared to the pre-existing condition of the institution. Significant moderate correlations were found between the creation of the REXIN office and the quality of agricultural education (r=0.3198, P-value=0.0113, alpha=0.05). Based on the results, the study recommends the improvement of the teaching of research-related subjects, conducting more training and updating of research mentors or advisors, and improving the preparation of research reports aligned with the standards.